Serum peptidomic profiling and peptide mass fingerprinting reveal signatures associated with peroxisomal and mitochondrial pathways in MMVD-associated cardiorenal syndrome in dogs - Poonavit Pichayapaiboon; Sekkarin Ploypetch; Walasinee Sakcamduang; Sittiruk Roytrakul; Janthima Jaresitthikunchai; Narumon Phaonakrop; Wachira Trakoolchaisri; Ruangrat Buddhirongawatr (PLoS ONE, 2026)
Cardiorenal syndrome in dogs, particularly those with myxomatous mitral valve degeneration (MMVD), involves complex neurohormonal interactions, yet molecular mechanisms linking heart and kidney dysfunction remain poorly understood. This study aimed to identify serum peptide and protein signatures that differentiate disease stages and clarify pathophysiology. We hypothesized that alterations in the serum peptide mass fingerprint and protein profile would serve as sensitive biomarkers for kidney disease progression in MMVD-affected dogs. Dogs were classified into five groups following ACVIM consensus guidelines for the diagnosis and treatment of myxomatous mitral valve disease in dog and IRIS Staging of chronic kidney disease (CKD): Healthy, MMVD Stage B1, MMVD Stage C without azotemia, MMVD Stage C with azotemia, and CKD IRIS Stage 2. Serum peptide profiling was performed using Matrix-Assisted Laser Desorption/Ionization – Time-of-Flight Mass Spectrometry (MALDI-TOF MS) for peptide mass fingerprint analysis and Nanoscale Liquid Chromatography-Tandem Mass Spectrometry for protein identification. MALDI-TOF MS effectively discriminated healthy dogs from diseased groups through discrete clustering in Partial Least-Squares Discriminant Analysis plots. Proteomic profiling identified 100 statistically significant proteins, with a critical subset of shared proteins including Peroxisomal biogenesis factor 14, Glutaredoxin-2, Creatine kinase mitochondrial 2, and Selenocysteine insertion sequence-binding protein identified between the MMVD C WAZ and CKD Stage 2 groups. These proteins are associated with the arginine and proline metabolism and peroxisome pathways, which were found to be influenced by standard medications such as pimobendan, furosemide, spironolactone, benazepril, and sildenafil. These findings reflect a systemic failure of cellular redox and energetic homeostasis driven by renin angiotensin aldosterone system activation and oxidative stress. The convergence of peroxisomal and mitochondrial dysfunction suggests a unifying mechanism for parallel cardiac and renal deterioration. These proteomic markers persist despite standard medical therapy, highlighting their potential as auxiliary tools for risk stratification and the monitoring of treatment efficacy in canine cardiorenal syndrome.